VIBRATORY CONVEYOR FOR LOADING FOOD MIXTURE MIXER - SPIRIN, ANATOLY; VOLYNETS , YEVHENII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The uniform supply of components to the mixing chamber is one of the main keys to the high-quality performance of this technological process. Currently, there is a lack of reliable feeders for mixers of food mixtures, especially of low productivity. This led to conducting analytical studies that make it possible to develop an effective design of the feeder, to determine the rational parameters of its work. As the analysis of the existing designs of feeders for loose materials showed, the problem of providing dosed supply of seeds or other particles in small volumes to the working chamber of the mixer can be solved by using oscillating conveyors, in which the transportation process is carried out due to high-frequency oscillations with a small amplitude. Depending on the operating modes, the material can move in the oscillating conveyor without detachment from the working surface (inertial conveyors) or with detachment (vibratory conveyors). Studies have shown that the most effective in terms of ensuring a stable material supply is the detachable mode of operation of bulk material feeders (vibratory type of feeders). In addition, this mode of operation helps to create a fluidized bed of material, which also increases the reliability of the feeders. The analysis of the movement of the seed along the oscillating plane made it possible to determine the influence of the main factors on the rational parameters that ensure a reliable dosed supply of the seed mass to the mixer of low productivity. The use of the proposed vibrating feeder scheme allows for the required performance, but significantly complicates the design of the food mixer. The conducted analytical and experimental studies made it possible to propose rational constructive and technological parameters of the feeder for the mixer of food mixtures of low productivity. It should be noted that when determining the nature of the movement of the seed mass along the oscillating plane, it is necessary to take into account the effect of the fluidized bed, which is the subject of additional research.